Use of medium chain fatty acids and a phytocomplex in diets for rabbit does - Meinieri, G.; Masoero, G.; Forneris, G. (Progress in Nutrition, 2013)
SummaryIn the present work, four diets for lactating female rabbits have been compared: diet C, control diet; diet A, containing a “blend” of medium chain fatty acids (Biotrade S.N.C.); diet P, containing extracts plants oil (Glycine S., Menta P., Malus P., Centaurium U.) (Probiotan®, by Biorama S.A.S.); diet M, diet containing three antibiotics (Colistine, Avylamicine, Tiamuline) used for the prevention of diseases. The 4 diets were administered to 63 female rabbits that had given birth to 452 pups, alive at 3 days post partum. The purpose of this study was to determine the survival rate of suckling rabbits. A highly significant (P: 0.002 ÷